Comparison of Growth Characteristics and Genomics of Two Canine Distemper Virus Strains Isolated From Minks in China - Tao, Rongshan; Chen, Jie; Zhao, Tianyu; Gong, Chengyan; Pan, Hongjun; Akhtar, Rana Waseem; Li, Xue; Shah, Syed Aftab Hussain; Li, Qingjie; Zhao, Jianjun (Frontiers in Veterinary Science, 2020)
Canine distemper (CD), caused by the CDV variant strain with HI542N/Y549H, has become an epidemic in fur-bearing animals in China since 2012. To well understand the genomic and replicated characteristics of the CDV variants, we determined the viral growth kinetics and completed the genome sequences of two CDV strains, namely SDZC(17)M2 and LNDL(17)M4, isolated from CDV-infected minks from Shandong and Liaoning province in China, in 2017. SDZC(17)M2 showed higher viral titers and extensive syncytia in BHK-minkSLAM (BMS) cells than LNDL(17)M4. Although both two strains belong to the Asia-1 genotype and clustered an independent clade in the phylogenetic tree, SDZC(17)M2, harboring I542N/Y549H substitutions in the H protein, shared high identity (99.3–99.6% nt) with the other variant strains, whereas LNDL(17)M4, with the only Y549H substitution, shared a lower identity (97.7%–97.9% nt) with the other variant strains. Furthermore, a novel R223K substitution was identified in the conserved cleavage site (RRQRR → RRQKR) of the F protein in the SDZC(17)M2 strain. However, it which did not significantly affect the cell to cell fusion activity when combined with the CDV H/minkSLAM in BHK-21 cells. The key variations in the genome contributed to the virulence and the evolutionary trend need to be determined in the future.